FURTHER STUDIES OF RADIATION PARAMETERS ON THE MICRODISTRICT PEREMOHA-6 (World Science, 2022)
The article reflects a further study of radiation parameters in the microdistrict of Peremoha - 6 in Dnipro city. Construction materials used as load-bearing, self supporting and external structures of residential and public buildings are made from mineral raw materials and industrial waste. The main building material used to build many residential areas of Dnipro city is heavy concrete (precast concrete, block or panel residential buildings), which accounted for 70-85% of the total construction industry. The issue of studying radiation parameters in residential and public buildings is relevant and its solution is aimed at determining the actual state of affairs in the field of radiation safety of construction projects of Peremoha-6, which are in operation, excluding new buildings and buildings currently under construction and have stricter requirements for radiation and environmental safety. The purpose of the work is to continue conducting systematic radiation surveys of buildings and structures of the housing stock, based on studies of the real level of the radiation background of residential buildings in operation. As a result of experimental studies and calculation of the external and internal components of the total radiation dose, it was found that the values of regulated radiation parameters formed from sources of ionizing radiation of man-made origin and the general radiation background they create in the premises of Peremoha-6 , exceeds the normative indicators for category B, which requires reducing the value of the total radiation dose of the population, based on the implementation of architectural-planning and technical radiation protection measures.